Financial management - Kolb, Robert W.; Rodríguez, Ricardo J. (Cambridge, MA : Blackwell Business, 1996)
This book presents: Financial Management and the Business Environment, The Time Value of Money: Single Payments, Stock Valuation...
Keywords: Finance; Business enterprises; Corporations; Finmaster; Corporations -- Finance; Business enterprises -- Finance -- Case studies; Corporations -- Finance -- Computer-assisted instruction; Finmaster